Human Development from Concept "Soft Skills" Communication - Emilawati Binti Othman; Masfizaizan Binti Manaf (Jurnal Konseling dan Pendidikan, 2018)
The program and planning as well as the transformation of human development in education at the Ministry of Higher Education Malaysia are aimed at producing a workforce capable of competitiveness and quality. This transformation aims to meet the demands and needs of human resources in addition to produce disciplined graduates, supporting the national aspirations and noble character. In the concept of "soft skills", communication is an essential element of self-development, generating knowledge, and competency. Therefore applying communication skills is needed, especially in the context of interpersonal, writing, presentation, training and consulting. To strengthen communication skills, more comprehensive and intensive approach are applied in polishing soft skills performance when planning, organizing, leadership or controlling. In this regard, human resource management dominates the careful planning and maximizes energy to be applied towards achieving a systematic and efficient communication skills and expertise in order to improve the quality of life and to protect the well-being of mankind. In order to realize this study, various metadological methods have been highlighted for intensive them is to distribute questionnaires to students of IPS who are currently undergoing the PUB2014 module, Human Development, adapting the theory learned by exposing the students IPS2-S1 to Demong Beach Resort Besut, Terengganu and students of IPS2-S2 went to the Woman's Welfare Association and Poverty Permata Al-Insyirah, Kuantan. Students were also given assignments and present the findings of the theory that have been learned and applied through "oral presentation" and using the IBM SPSS Statistics version 23 instrument to analyze the distributed questionnaire data. The findings of human development studies from the concept of "soft skills" find that human resource development is regarded as a lubricant as well as a generator within an organization also a catalyst for changes in human resource behavior within the organization, especially the students of IPS2-S1 and IPS2-S2 in Politeknik Sultan Mizan Zainal Abidin (PSMZA). This is because IPS students have developed effective and productive communication skills for orphans and their environment.